Influence of Ceramic Material Type and Cement Shade on the Translucency of Lithium Disilicate Ceramic Veneers - Ali Dhahee Malallah; Nadia H. Hasan; Mohammed Hazim Qasim (Wiley, 2024)
Conclusions: Different shades of resin cements and different manufacturing techniques produce different levels of color changes therefore careful selection of materials and cement shade can minimize color changes in laminate veneers.